Writings - Washington, George 1732-1799 (Library of America, 1997)
Among the early writings included are the journal Washington kept at age 16 while surveying the Shenandoah Valley frontier and his dramatic account of the winter journey he made through the Pennsylvania wilderness in 1753 while on a diplomatic mission